GAYA KEPEMIMPINAN DAN KINERJA KARYAWAN: TINJAUAN LITERATUR - Danang Nugroho; Anggita Nahwa Firdausi; Edgina Hartahartina; Nurul Maulani Hasanah; Melati Rahma Anggraeni (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research conducts a literature review to explore the relationship between leadership styles and employee performance using qualitative research methods. Through in-depth analysis of various literature sources, including journal articles, books, and research reports, this study aims to understand the complex dynamics between leadership styles and employee performance from a qualitative perspective. A qualitative approach is used to explore the context and nuances underlying the relationship between leadership styles (such as transactional, transformational, and situational) and employee performance in various organizational situations. The findings from this literature review provide a deeper understanding of the impact of leadership styles on performance through factors such as motivation, communication, personal development, and social support. The practical implications of these findings for leadership development and human resource management are also discussed. This research contributes to our understanding of the complexity of the relationship between leadership styles and employee performance, while providing a basis for further research in this domain.